Analysis Of Physics Test Items For Grade XI Using The Rasch Model At SMAN 1 Sape - Sumiharsono, Rudy (UNIVERSITAS PAKUAN, 2025)
Assessment is an integral part of the learning process, aiming to measure the achievement of educational objectives. High-quality assessment instruments require evaluation of item validity, reliability, and difficulty level. This study aims to analyze the quality of Physics test items for grade XI at SMAN 1 Sape, Bima Regency, using the Rasch Model. This approach was selected because it provides detailed information on item characteristics, including validity, reliability, and difficulty, in a quantitative manner. The study employed a descriptive quantitative method. Data were collected from midterm examination results of grade XI students from purposively selected schools. A total of 25 multiple-choice items were analyzed using WINSTEP software with the Rasch Model approach. The analysis was conducted to identify items that were valid, reliable, and appropriately difficult according to students' ability profiles. The results showed that most items lacked adequate validity and required revision. The reliability of the instrument was categorized as moderate, indicating a sufficient level of consistency in measuring students' abilities. Regarding item difficulty, most questions were classified as difficult, with only a few categorized as easy or very easy. These findings underscore the importance of regular evaluation of test items to ensure the quality of assessment instruments.